Pengaruh Kepemilikan Manajerial, Kepemilikan Publik, Leverage, Firm size, dan Operating Cash Flow Terhadap Konservatisme Akuntansi - Maya Widyana Dewi; Yuge Agung Heliawan (ITB AAS INDONESIA, 2021)
This study aims to determine the effect of managerial ownership, public ownership, leverage, firm size, and operating cash flow on accounting conservatism in manufacturing companies on the Indonesia Stock Exchange in 2016-2018 partially and simultaneously. The method in this study uses descriptive quantitative. The population in this study are manufacturing companies in the consumer goods industry sector that have been registered and published financial reports on the Indonesia Stock Exchange (IDX) in 2016-2018. The research population is 47 companies. The sample in the study was 21 companies with a sampling technique using purposive sampling technique. The data used is secondary data from the official website www.idx.com. The data analysis method used descriptive statistical tests and classical assumption tests, while the hypothesis testing used multiple regression analysis, F test, t test, and coefficient of determination test. The results showed that the five independent variables used by managerial ownership, public ownership, leverage, firm size, and operating cash flow simultaneously affect accounting conservatism. Based on the partial test, managerial ownership has no significant effect on accounting conservatism, while the other four variables, namely public ownership, leverage, firm size, and operating cash flow, have a significant effect on accounting conservatism. The five independent variables used are managerial ownership, public ownership, leverage, firm size, and operating cash flow simultaneously have an effect on accounting conservatism.